Geology of the Sheguiandah Early Man Site: Key Concepts and Issues - E. Lee, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTThe first indication that man was present in Canada well before the final retreat of glacial ice was found at the village of Sheguiandah, on Manitoulin Island, Ontario, in the early 1950s. This paper summarizes the relevant evidence and arguments. The key deposits are two thin layers of diamicton toward the top of the glacial sequence, immediately below a post-glacial level characterized by Paleo-lndian projectile points. The unsorted mixtures of clay, sand and stones contain undisputed quartzite artifacts. These diamictons are considered to be till; alternatives, such as mixing by frost action and mud flows, do not explain their origin. The means by which the artifacts survived the Laurentide glaciation are suggested by the orientation and dip of the pebbles. Apparently diverted from its normal direction of flow by a tough quartzite knob, the ice lacked much erosive power at this point, only transporting the artifacts from one part of the site to another. Geological interpretation indicates that man made the artifacts now found in the tills during Early Wisconsinan interstadials. Other evidence, in the form of prehistoric quarries, pollen analyses and radiocarbon dating, supports the published age estimate of more than 30,000 years BP.